2017
DOI: 10.1590/1982-0224-20170055
|View full text |Cite
|
Sign up to set email alerts
|

Migration and brackish environment use of Prochilodus lineatus (Characiformes: Prochilodontidae) inferred by Sr:Ca ratio transects of otolith

Abstract: The streaked prochilod, Prochilodus lineatus, represents the most important fishery in the La Plata Basin (South America). Our objective was to analyze brackish environment use by the streaked prochilod captured from Paraná and Uruguay rivers. To accomplish this, lapillus otolith sections were analyzed for Sr:Ca with laser ablation-inductively coupled plasma-mass spectrometry (LA ICP-MS) to infer habitat use of fish. To the interpretation of transects, a threshold that represents the transition between freshwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Estimates of stock composition showed that the degree of mixing was higher for adult fish (2014) compared with the subadults (2012), considering the estimations made with MLE and MCL (Figure ). Avigliano, Pisonero, et al () reported that between 5% and 37% of the fish caught in the Uruguay and Paraná rivers use the estuary once in their lives, migrating at least 1,000 km from the capture areas (next to nursery areas here studied). These large displacements were observed in individuals older than 3 years (Avigliano, Pisonero, et al, ).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Estimates of stock composition showed that the degree of mixing was higher for adult fish (2014) compared with the subadults (2012), considering the estimations made with MLE and MCL (Figure ). Avigliano, Pisonero, et al () reported that between 5% and 37% of the fish caught in the Uruguay and Paraná rivers use the estuary once in their lives, migrating at least 1,000 km from the capture areas (next to nursery areas here studied). These large displacements were observed in individuals older than 3 years (Avigliano, Pisonero, et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Avigliano, Pisonero, et al () reported that between 5% and 37% of the fish caught in the Uruguay and Paraná rivers use the estuary once in their lives, migrating at least 1,000 km from the capture areas (next to nursery areas here studied). These large displacements were observed in individuals older than 3 years (Avigliano, Pisonero, et al, ). Other authors indicated the dominance of specimens between <1 and 3 years in some environments such as streams, associated floodplains, and lagoons, whereas older specimens (4 or 5 years and older) were dominant in the main course of Paraná (Sverlij et al, ).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations